Advanced Model Compounds for Understanding Acid-Catalyzed Lignin Depolymerization: Identification of Renewable Aromatics and a Lignin-Derived Solvent - Lahive, Ciaran W.; Deuss, Peter J.; Lancefield, Christopher S.; Sun, Zhuohua; Cordes, David B.; Young, Claire M.; Tran, Fanny; Slawin, Alexandra M. Z.; de Vries, Johannes G.; Kamer, Paul C. J.; Westwood, Nicholas J.; Barta, Katalin (Journal of the American Chemical Society, 2016)
The development of fundamentally new approaches for lignin depolymerization is challenged by the complexity of this aromatic biopolymer. While overly simplified model compounds often lack relevance to the chemistry of lignin, the direct use of lignin streams poses significant analytical challenges to methodology development. Ideally, new methods should be tested on model compounds that are complex enough to mirror the structural diversity in lignin but still of sufficiently low molecular weight to enable facile analysis. In this contribution, we present a new class of advanced (beta-O-4)-(beta-5) dilinkage models that are highly realistic representations of a lignin fragment. Together with selected beta-O-4, beta-5, and beta-beta structures, these compounds provide a detailed understanding of the reactivity of various types of lignin linkages in acid catalysis in conjunction with stabilization of reactive intermediates using ethylene glycol. The use of these new models has allowed for identification of novel reaction pathways and intermediates and led to the characterization of new dimeric products in subsequent lignin depolymerization studies. The excellent correlation between model and lignin experiments highlights the relevance of this new class of model compounds for broader use in catalysis studies. Only by understanding the reactivity of the linkages in lignin at this level of detail can fully optimized lignin depolymerization strategies be developed.